"It's a gap in awareness": Exploring service provision for LGBTQ2S survivors of intimate partner violence in Ontario, Canada. Issue 4 (2nd October 2017) - Furman, Ellis; Barata, Paula; Wilson, Ciann; Fante-Coleman, Tiyondah
ABSTRACT: Intimate partner violence (IPV) is a prevalent issue in all relationship configurations, including lesbian, gay, bisexual, transgender, queer, and two-spirit (LGBTQ2S) relationships. While the experiences of LGBTQ2S IPV survivors are understood, there are issues, needs, and challenges associated with service provision for them. Semi-structured interviews were conducted with a sample (N = 10) of professionals (e.g., counselors, shelter managers, program directors) affiliated with organizations that provide services for IPV survivors in Ontario, Canada. Participants answered questions pertaining to the inclusion of LGBTQ2S IPV survivors into their existing services, and what service provision should look like. Data was analyzed using a thematic analysis to uncover themes that reflected participants' responses. The data was organized into recommendations for service provision at three different levels: direct service provision, organizational transformation, and underlying principles and values. Findings reveal suggestions for service providers to consider modifying their current organizations, to adequately include LGBTQ2S IPV survivors.